Evaluasi Program Wirid Remaja Dengan Model CIPP di SLTA Kota Payakumbuh - Helfyna Desrita; Iswantir Iswantir (Media Manajemen Pendidikan, 2026)
This study aims to evaluate the effectiveness of the adolescent wirid program at Payakumbuh City High School using the CIPP (Context, Input, Process, Product) model as a comprehensive analysis framework for the policy of fostering students' religious character. This program is an initiative of the West Sumatra Provincial Government in strengthening the morals of the younger generation in the digital era. The study used a quantitative approach with an evaluative method on 354 grade XI students selected from a population of 3,150 students through the Slovin formula with an error rate of 5%. Data were collected through Likert scale questionnaires, interviews, and documentation, then analyzed using descriptive statistics. The results of the study show that the context aspect of the program is very relevant to the spiritual needs of students, the input aspect is considered quite adequate even though it requires method innovation, the process aspect runs consistently but still faces participation obstacles, and the product aspect shows a positive impact on worship discipline and the formation of religious character. Overall, the youth wirid program is considered effective and feasible to continue with strengthening monitoring, improving the quality of presenters, and continuous collaboration between schools, families, and communities.